EFFECTIVENESS OF CORE STABILITY EXERCISES AND GENERAL EXERCISES IN THE MANAGEMENT OF CHRONIC LOW BACK PAIN: A RANDOMIZED CONTROLLED TRIAL - Syed, Shafaq; Khan, Danish Ali (Annals of Allied Health Sciences, 2016)
AIM: The aim of clinical trial was to determine the effectiveness of core stability exercises and general exercises in the management of chronic low back pain. METHODOLOGY: A total of 60 patients (including both male and female), aged 20-60 years, diagnosed with chronic low back pain were randomly allocated to core stability exercise and general exercise groups. Patients were recruited through consecutive sampling technique. Baseline assessment of all the patients was done before assigning to the patients to either of the groups. Patients in both groups were assessed after 4 weeks on tools assessing pain and physical activity level for comparing the final outcomes of both exercises regimes. RESULTS: There were no differences amongst the outcome of both groups in pain intensity and disability. The effectiveness of both core stability exercises and general exercises showed a significant reduction in pain intensity (p=0.000) for the patients in both groups. Similarly, means of functional disability was also decreased significantly in both core stability group and general group (p=0.000). CONCLUSION: Both physical therapy regimes produced a clinically important improvement in pain and disability index, so the selection of technique for the management of CLBP can be based on the individual needs.